THE INFLUENCE OF THE SOCIAL ENVIRONMENT ON MOTHER'S COMPLIANCE IN IMPLEMENTING BASIC IMMUNIZATION IN BABIES - Yanti, Dian Anggri (JURNAL KESMAS DAN GIZI (JKG), 2023)
The immunization program aims to control the health and safety rates of children under five from the threat of various diseases related to infection. Very often, mothers are disobedient in immunizing their babies because they are influenced by perceptions or views from the social environment. The social environment exists in the family, peers and neighbors which can influence the attitudes and actions of a person or group in carrying out an activity. Meanwhile, immunization is very important for babies in an effort to prevent disease and increase toddlers' immunity. This type of research is descriptive quantitative research using a cross-sectional approach, which aims to describe the situation in depth and systematically. The sample consisted of 30 mothers. The instrument used was a questionnaire to measure social environmental factors and maternal compliance with basic immunization. The research data obtained was analyzed using univariate and bivariate analysis. The research results showed that as many as 11 mothers (36.7%) who were in a good social environment tended to comply with the implementation of infant immunization. Meanwhile, 16 mothers (53.3%) who were in poor social environments tended to be disobedient to the implementation of infant immunization. The p value of 0.000 < 0.05 in the chi-square test shows that the social environment has a significant effect on maternal compliance in implementing basic immunization for babies in Sidodadi Ramunia Village. Mothers who live in a good social environment tend to comply with the implementation of infant immunization.